Proceedings of the National Conference on Water, Food Security and Climate Change in Sri Lanka, BMICH, Colombo, Sri Lanka, 9-11 June 2009. Vol. 2. Water quality, environment and climate change - Evans, Alexandra E.V.; Jinapala, K. (International Water Management Institute, 2010)
This is the second volume of the proceedings of the National Conference on ?Water for Food and Environment?, which was held from June 9 ?11, 2009 at the Bandaranaike Memorial International Conference Hall (BMICH). The volumes 1 and 3 have been produced as separate documents of this report series. In response to a call for abstracts, 81 abstracts were received from government institutes dealing with water resources and agriculture development, universities, other freelance researchers and researchers from the International Water Management Institute (IWMI). Forty seven of the eighty-one abstracts that were submitted were accepted for compiling full papers.